AB0295 Abnormal Central Retinal Vein Equivalent Found in Active Rheumatoid Arthritis: A Different Perspective of Microvascular Health. (15th July 2016) - Babaoglu, H.; Kadayifcilar, S.; Erden, A.; Baytaroglu, A.; Kalyoncu, U.
Abstract : Background: Patients with rheumatoid arthritis (RA) have increased risk of cardiovascular disease. Retinal vascular caliber (RVC) is one of the new tools to determine the cardiovascular risk. RVC includes central retinal artery and vein equivalents (CRAE and CRVE). It is well known that CRVE is closely related with chronic inflammation (1). Objectives: The objective of this study was to assess RVC score in RA patients and compared the data with those of SLE patients and age-sex-comorbidity equivalent population. Methods: Forty-seven RA patient were enrolled in this study between July 2014 and January 2015. Demographic data of patients were recorded. Before the measurement of RVC, disease activity was measured by Disease Activity Score-28 (DAS-28). Functional capacity assessed by Health Assessment Questionnaire (HAQ). Disease activity was categorized according to DAS-28 (DAS-28<3.2 low disease activity, DAS-28>5.1 high disease activity). Thirty-two SLE patients and 45 healthy controls constituted the control groups. RVC was measured from the dilated fundus photographs, and summarized as the central retinal artery and vein equivalents (CRAE- CRVE) using a semi-automated computer-assisted method (IVAN, Wisconsin University-Figure 1 ). Measurement of the retinal vascular caliber performed in between the 0, 5–1 disc distance from the optical disc margin (Zone B, figure 1 ). Arterioles and venules were marked semi-automatically by the software (Red=arterioles, Blue=Venules). The largest 6 vessels width used in the previously accepted formula for calculating the CRAE and CRVE. Retinal photography was performed in all patients at baseline and 24 of RA patients were re-evaluated 5.2±2.1 months later. Results: The mean age of RA, SLE patients and healthy controls were 52.1±11.9, 41.4±14.5, and 47.2±17.3 (p=0, 008), respectively. Female sex (83%, 84%, and 80%, p>0.05), hypertension (40%, 31%, and 27%, p>0.05) and diabetes mellitus (8%, 3%, and 11%, p>0.05) frequencies were similar in all groups. CRAE score was similar in RA, SLE, and healthy controls (147.8±11.7 μm, 148.3±12.8μm, and 147.4±17.6μm), respectively. CRVE score was also similar (213.3±17.8 μm, 209.2±14, 1μm, and 217.5±26.2μm). There was no correlation between DAS-28, HAQ score with RVC scores. At baseline, ten (21%) of patients had active disease, and 22 (47%) patients had low disease activity. CRVE score was higher in active RA patients than low disease activity patients (222.8±10.1 vs. 207.3±17.8, p=0.004). There was no correlation between the changes of DAS-28 and HAQ with the RVC changes during follow-up period. Conclusions: CRVE is associated with systemic inflammation and possibly increased CV risk (1, 2). Although, CRVE and CRAE were similar in RA, SLE and healthy control groups, however especially active RA patients had worse CRVE level. Measurement of retinal vein caliber is a sensitive methods for assessment of microvascular circulation. Further studies should be focused to importance of abnormal CRVE and cardiovascular status in rheumatic diseases. References: Archives of Ophthalmology 2006;124:87–94. Annals of Internal Medicine 2009;151:404–13. Disclosure of Interest: None declared